„NAJWIĘKSZA TAKA KATASTROFA…” O NIEWIDOCZNYCH REPREZENTACJACH KATASTROFY ELEKTROWNI JĄDROWEJ W CZARNOBYLU - Brylska, Aleksandra (Studia Europaea Gnesnensia, 2018)
The paper asks how the actually invisible event of the Chernobyl disaster is remembered and represented. The author therefore examines the discourse concerning the events of April 26th, 1986: how it developed, changed over the transformation period, and subsequently functioned until the present day.